2011
DOI: 10.1001/jama.2011.1246
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Cathepsin S and Mortality in Older Adults

Abstract: Among elderly individuals in 2 independent cohorts, higher serum cathepsin S levels were associated with increased mortality risk. Additional research is needed to delineate the role of cathepsin S and whether its measurement might have clinical utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 46 publications
3
45
1
1
Order By: Relevance
“…It was known that plasma Cat-S levels correlate with age, CV disease, and diabetes [7][8][9][10][11]14 and that the proteolytic activity of Cat-S can degrade elastic fibers (e.g., during the progression of macrovascular diseases). 19 As a new finding, the results of our experiments identify a previously unknown biologic function of Cat-S (i.e., its agonistic activity of PAR2 on the surface of endothelial cells).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was known that plasma Cat-S levels correlate with age, CV disease, and diabetes [7][8][9][10][11]14 and that the proteolytic activity of Cat-S can degrade elastic fibers (e.g., during the progression of macrovascular diseases). 19 As a new finding, the results of our experiments identify a previously unknown biologic function of Cat-S (i.e., its agonistic activity of PAR2 on the surface of endothelial cells).…”
Section: Discussionmentioning
confidence: 99%
“…6 Diabetes and CV diseases are associated with increased plasma levels of the cysteine protease cathepsin S (Cat-S), and its elastolytic properties contribute to CV mortality. [7][8][9][10][11][12] Cystatin C limits the extracellular proteolytic activity of Cat-S to approximately 1%. 13 Cat-S induction or cystatin C suppression tilts this balance toward degeneration of the vascular wall, 14 which drives progressive CV disease and all-cause mortality in patients with CKD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In obese men, higher CS serum levels were associated with higher pro-inflammatory cytokines like IL-6 and an increase of hs-CRP [22]. Additionally, higher CS serum levels were associated with decreased insulin sensitivity and higher mortality in two cohorts of elderly people [23,24]. Recently, it was shown that CS serum levels were higher in patients with gastric cancer and that serum CS levels correlated with the tumour volume [25].…”
Section: Discussionmentioning
confidence: 99%
“…The following quantities were later measured: lipoproteins (total cholesterol, HDL cholesterol, LDL cholesterol, triglycerides, apoprotein A1, apoprotein B), high-sensitivity c-reactive protein (hs-CRP) [15], YKL-40 [16], highsensitive assay cardiac troponin T (hs-cTnT) [17], pregnancy associated plasma protein-A (PAPP-A) [18], Nterminal pro-B-type natriuretic peptide [17], cathepsin B [19], endostatin [20], cathepsin S [21], soluble TNF receptor 1 and 2 (sTNFR1 and sTNFR2) [22], neutrophil gelatinase-associated lipocalin (NGAL) [23], calprotectin [24], osteoprotegerin [25], and glomerular filtration rate using creatinine (GFR) [26].…”
Section: The Datamentioning
confidence: 99%